Retrospective Analysis of Psychological Factors in COVID-19 Outbreak Among Isolated and Quarantined Agricultural Students in a Borneo University - Muhamad, Assikin Bin; Pang, Nicholas Tze Ping; Salvaraji, Loganathan; Rahim, Syed Sharizman Syed Abdul; Jeffree, Mohammad Saffree; Omar, Azizan (Frontiers in Psychiatry, 2021)
Introduction: Much has been known about the psychological issues that can emerge in people who are quarantined and unable to move freely. The COVID-19 pandemic has no contrast from previous outbreaks like SARS and MERS regarding their ensuing worries and boosted anxiety levels. This article seeks to examine the unique psychological changes that occur in students who have been quarantined inside a university campus and assess sociodemographic factors associated with certain psychological factors. Methodology: The data was collected from students in an Agricultural Campus. In the first phase, the factor structure of the modified National Index Psychological Wellness (NIPW) was acceptable, and to establish statistical parameters for validation an exploratory factor analysis was done. In the second phase, Independent T-tests, ANOVA, and Hierarchical Multiple regression were performed. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 26.0. Result/Discussion: A total of 46 male and 76 female students enrolled in this study. The Bartlett's test of sphericity was significant (p < 0.001) and the Kaiser–Mayer–Olkin measure of sampling adequacy for the AUDIT-M was 0.901. The Cronbach's alpha of the entire modified NIPW was 0.657 which suggests reasonable internal consistency and subscales between 0.913 and 0.924. Raw scores of 12 positive items were higher for the quarantined group except for “I can do daily routines,” “I understand what happens,” and “I understand the action that is performed is fair.” Raw mean scores of eight negative scoring items were higher in the quarantined group, except for “I feel angry” (2.88 vs. 2.89 for non-quarantined group). There were statistically significant differences between year groups for the questions “I understand what happens,” “I understand the action that is performed is fair,” and “I think everyone is good.” Conclusion: Movement control orders or compulsory quarantine orders can be distressing and may cause understandable psychological sequelae. Holistic management of a quarantine center that addresses the needs and health of an individual student will give a positive impact on psychological wellness. Quarantining facilities can be a place of positivity, allowing people to live a shared experience together, provide peer support for each other, and give each other hope.